Artificial intelligence is important! A mini systematic literature review of bioethics in science learning - Atok Miftachul Hudha; H. Husamah; Intan Kristina Permatasari; Mella Anggi Puspitasari; S. Silvia (Universitas Muhammadiyah Malang, 2024)
The focus and concern of researchers on the theme of bioethics and its relationship with science learning is highly expected, as evidenced by publications in reputable journals. The purpose of this systematic literature review (SLR) was to review and compare investigations of researches on article published by scopus indexed journals. We used the phrase